Parallelizing dynamic programming through rank convergence - Maleki, Saeed; Musuvathi, Madan; Mytkowicz, Todd (2014 ACM SIGPLAN Symposium on Principles and Practice of Parallel Programming, 2014)
This paper proposes an efficient parallel algorithm for an important class of dynamic programming problems that includes Viterbi, Needleman-Wunsch, Smith-Waterman, and Longest Common Subsequence. In dynamic programming, the subproblems that do not depend on each other, and thus can be computed in parallel, form stages or wavefronts. The algorithm presented in this paper provides additional parallelism allowing multiple stages to be computed in parallel despite dependences among them. The correctness and the performance of the algorithm relies on rank convergence properties of matrix multiplication in the tropical semiring, formed with plus as the multiplicative operation and max as the additive operation. This paper demonstrates the efficiency of the parallel algorithm by showing significant speed ups on a variety of important dynamic programming problems. In particular, the parallel Viterbi decoder is up-to 24x faster (with 64 processors) than a highly optimized commercial baseline.